DNA markers in oat breeding for crown rust resistance (a review) - A. V. Bakulina; N. V. Novoselova; L. S. Savintseva; G. A. Batalova (Труды по прикладной ботанике, генетике и селекции, 2022)
Crown rust is the most harmful disease of oat (Avena sativa L.) around the world. The purpose of this review is to analyze and generalize the available information about DNA markers developed for oat breeding for resistance to crown rust. The review reveals the mechanisms of the A. sativa resistance to the fungus Puccinia coronata Corda f. sp. avenae Erikss. which causes crown rust disease. Special attention is paid to the race-specific resistance caused by the action of Pc genes and the nonspecific resistance controlled mainly by the loci of quantitative traits. Strategies for creating resistant genotypes and the role of molecular markers in oat breeding for crown rust resistance are discussed. Currently, research is focused mainly on the search for and development of molecular markers related to the oat race-specific resistance to P. coronata.The article presents the technological advantages and disadvantages of the existing DNA markers. KASP, TaqMan and HRM markers are currently the most promising technologies for identifying crown rust resistance genes. The validated SCAR and STS markers for the Pc39, Pc68, Pc91, Pc94 genes are recommended as the most available for implementation in practical oat breeding. The results of recent studies on identifying loci of nonspecific resistance to P. coronata are also presented. In general, the use of DNA markers has significant potential for creating oat genotypes resistant to crown rust under present-day conditions. DNA markers of various types are recommended for practical use, in particular for pyramiding genes and increasing the resistance period of new cultivars. Introduction of DNA markers into oat breeding will increase with the growth of molecular genetic data and the improvement of technologies for identifying genes and loci associated with both race-specific and nonspecific resistance of oat to P. coronata.